Mengenal Dan Memahami Notasi Penulisan Dalam Algoritma Pemrograman - Bulan Naysabilla; Yahfizham Yahfizham (Politeknik Kampar, 2023)
Programming is a way that can be used in instructing computers to carry out certain tasks. Computer instruction means providing a set of commands that can be notated in a language understood by the computer. A program is a set or series of instructions to solve a problem. While the algorithm is a sequence of logical instructions in solving a problem that is arranged systematically. The purpose of this research is to facilitate the community, especially from students and students in the notation of writing programming algorithms on computer use. For the writing of this journal, the author uses the method of literature research among others by reading and studying books, articles, laws and other literature sources related to problems in this journal. From the results of the study, it can be shown that programming algorithms have three ways to notify the writing of programming algorithms, namely by means of descriptive sentences, flowcharts and pseudecode.